Now more than ever - Huxley, Aldous, 1894-1963 (Harry Ransom Humanities Research Center imprint series., 2000)
"Written in 1932-1933 immediately after Huxley had completed Brave New World, Now More Than Ever is a response to the social, economic, and political upheavals of its time. Huxley's protagonist is an idealistic financier whose grandiose scheme for industrial renewal drives him to swindling and finally to suicide. His fate, which mirrors that of the notorious Swedish financier Ivar Kreuger, allows Huxley to expose the evils he perceives in free-market capitalism while pleading the case for national economic planning and the wholesale rationalization of Britain's industrial base."--Jacket.